Screening bioactives from vegetal sources as potential skin lightening agents using an enzymatic model of tyrosinase inhibition, correlations amongst activity, phenolic compounds content and cytotoxicity (2006)
ABSTRACT: For many people, irregularities in skin pigmentation had become an aesthetic problem, mainly when they are affecting the face. For this reason, there is a big interest in products with skin lightening properties for treating irregularly pigmented skin areas. Skin pigmentation, is the consequence of production and dispersion of melanin, a pigment sinthesized in epidermal melanocytes were the precursor amino acid tyrosine is sequentially oxidized into L-dihydroxyphenylalanine and dopaquinone by the copper-containing enzyme tyrosinase (EC 1.14.18.1), the key and rate limiting enzyme in melanin biosynthesis (1). In our search for tyrosinase inhibitors from plants, we study Ruta graveolens and citrus sinensis extracted by different means, for inhibition of the oxidation of L-3,4-dihydroxyphenylalanine (L-DOPA) catalyzed by mushroom tyrosinase and correlated activity with the content of phenolic compounds and its cytotoxicity. In our case, although phenolics could be the main compounds responsible for activity, no clear correlations exist between cytotoxicity, tyrosinase inhibition and the content of phenolic compounds, however the contents of this compounds increased as a more astringent method of extraction was used.